Characterization of nano- and micro-crystalline CdS synthesized using cyclic microwave radiation - Thongtem T. (2014)
Nano- and micro-crystalline CdS was synthesized from cadmium [CdCl2·2H2O, Cd(NO3)2·4H2O, Cd(CH3COO)2·2H2O] and sulfur [CH3CSNH2, CH5N3S, CH6N4S] sources in ethylene glycol assisted by cyclic microwave radiation at different conditions. Phases (hcp and cubic) and morphologies (rose-shaped particles, spikes in cluster, cauliflowers, and nano-particles in cluster) were detected using XRD, SAED, TEM, and SEM, and influenced by Cd and S sources. The crystalline products are aligned in a systematic array and analyzed by HRTEM. A Raman spectrometer revealed the presence of fundamental and overtone modes at 298 and 597 cm-1, respectively. Exposure times and microwave powers also play a role in the crystallinity and size of the products. © 2007 Elsevier Ltd. All rights reserved.